$10,000 in small, unmarked puzzles - Hall, Parnell (New York : Minotaur Books, 2012)
Stumbling over a murder scene while making a blackmail payment for a young attorney, Cora Felton's efforts to solve the crime put her in the path of a killer who may be targeting her niece and her niece's new baby.
"A Thomas Dunne Book.&quot
edited hb 2015-06-16
Keywords: Felton, Cora (Fictitious character) -- Fiction; Women detectives -- Fiction; Crossword puzzle makers -- Fiction; Mystery fiction